Proximal analysis of seagrass species from Laguna de Términos, Mexico - Coria-Monter, Erik; Durán-Campos, Elizabeth (HIDROBIOLÓGICA, 2015)
This paper examines chemical nutritional aspects of three seagrass species (Thalassia testudinum König, Halodule wrightii Ascherson, and Syringodium filiforme Kützing) found at Laguna de Términos, Campeche, Mexico during the rainy season of 2004, following analysis methods described by the Association of Official Analytical Chemists. High protein (8.47-10.43%), high crude fiber (15.70-19.43%), high ash (23.43-38.77%) high nitrogen-free extract contents (37.27-45.37%), and low lipid levels (0.83-2.13%) were common features of the three species analyzed. Given its chemical contents and the World Health Organization reference standards, particularly the high protein (10.43%), high ash (23.43%), high fiber (19.43%), high nitrogen-free extract (45.37%) and low lipids (2.13%), S. filiforme appears to be a noteworthy potential dietary supplement and a nutrient source for human consumption. Another use of this high-protein seagrass could be in producing food for aquaculture fish.